The Implementation of Strengthening Character Education Program through Scouts Extracurricular Activities in Islamic Senior High School 1 Pulang Pisau and Islamic Senior High School of Palangkaraya - Rahman, A.; Wasliman, I.; Hanafiah, Hanafiah; Iriantara, Y. (Journal of Education Research and Evaluation, 2021)
Noble character education for Islamic Senior High School (MAN) students is considerably related to school management. The management refers to how the noble character building is planned, implemented, and controlled by empowering the whole resources of the school and is reflected in the educational activities in the school. This research aims to discover the strengthening noble character education program of MAN students. In addition, it also examines the implementation and the impacts of strengthening noble character education programs of MAN students. This research applied a qualitative research method to conduct a case study in Islamic Senior High School 1 Pulang Pisau and Islamic Senior High School Palangkaraya. Eventually, this research identified that (1) the strengthening noble character education program of MAN students through Scouts extracurricular activities have not been implemented properly; despite the SOP of each activity, (2) the implementation of the strengthening noble character education programs of MAN students through Scouts extracurricular activities have not reached proper service quality due to the assessment system, (3) the impacts of the implementation of the strengthening noble character education program of MAN students through Scouts extracurricular activities have achieved the objectives; nevertheless, the impacts can only be monitored when the students are in the school.